Respuesta :

122095

your pic doesn't load in

Answer:

Step-by-step explanation:

a=3 b=5 c=8

solve the equations---

Section A :

1) ab+3c = (3)(5)+3(8) = 15+24 = 39

      [tex]ab + 3c = (3)(5) + (3)(8)=15+24=39[/tex]

2) 2a-3b = 2(3) - 3(5) = 6 - 15 = -9

      [tex]2a-3b=2(3)-3(5)=6-15=-9[/tex]

3) 2(a+b) - c squared = 2(3+5) - 8 squared = 2(8) - 64 = 16 - 64 = -48

      [tex]2(a+b) - c^{2} = 2(3+5) - 8^{2} =2(8) - 64 = 16 - 64 = -48[/tex]

4) 3a x 2b + 4c = 3(3) x 2(5) + 4(8) = 9 x 10 + 32 = 90 + 32 = 122

     

5) a squared - 2c = 3 squared - 2(8) = 9 - 2(8) = 9 - 16 = -7

       [tex]a^{2} -2c = 3 ^{2} - 2(8) = 9 - 2(8) = 9 - 16 = -7[/tex]

simplify the expressions---

          - pretty much distribute

Section B :

1) a(2a+b) = 2a squared + ab

      [tex]a(2a+b)=\\2a^{2} + ab[/tex]

2) 3(3g - 4) = 3 squared g - (3)4 = 9g - 12

    [tex]3 (3g-4)=\\3^{2} g - (3)4 =\\9g - 12[/tex]

3) 2a(4b - 2ad) = 8ab - 4a squared d

     [tex]2a(4b-2ad) = \\8ab-4a^{2} d[/tex]

4) -3ab(1 +5a) = -3ab -15a squared b

    [tex]-3ab(1+5a)= \\-3ab - 15a^{2} b[/tex]

5) k(3k + 14) = 3k squared + 14k

     [tex]k(3k + 14)=\\3k^{2} +14k[/tex]

hope this helps!

mark me brainliest :D